THE SPAСE OF EDUCATIONAL RESEARCH ACTIVITY OF STUDENTS BASED ON ASSOCIATION ONTOLOGICALLY INTERFACE AND GIS-TECHNOLOGIES - Maryna A. Popova; Svitlana M. Brevus (Інформаційні технології і засоби навчання, 2014)
This article discusses the ontologies and ontological computer interface use as an effective means of integration, aggregation and visualization of distributed information resources and systems through the use of semantic properties to create and use of information space in education and research activities of students. The approach of combining ontologies features and geospatial analytical tools functions of GIS is described. The technique of ontological interface applying by creating a thematic map layers in GIS environment based on thematic ontology is presented.